Effects of Heat Treatment Applied to Wood and Veneers of Various Wood Species - Emilia-Adela Salca (Advanced Research in Biological Science Vol. 2, 2023)
Wood is one of the most important renewable materials with excellent physical and mechanical properties. However, its dimensional instability due the hygroscopic behavior is one of the shortcomings of wood and wood products. To enhance such disadvantage of wood many studies have been carried out using different modification processes and among them heat treatment is the oldest, the least expensive, and the most eco-friendly modification method. In this chapter the effects of heat-treatment on the properties of solid wood and veneers from different wood species are evaluated. It is expected that the heat treatment can add potential value on wood material to be used more effectively in further manufacturing steps.